Determinants of Healthcare Utilization among Senior Citizens in Davao City, Philippines - Alipio, Mark; Pregoner, Joseph Dave (JPAIR Multidisciplinary Research, 2020)
As the number of senior citizens increases, issues regarding their utilization of healthcare services are becoming highly relevant to discuss. This study aims to evaluate the potential determinants of healthcare utilization among senior citizens in Davao City, Philippines. Stratified sampling with proportional allocation was employed to select the 2,952 respondents. Data were collected using questionnaires. Of the total sample, 61.0% consumed cigarettes at most two times per week, 70.0% drank alcohol two to three times per week, and 78.3% performed an exercise at most one time per week. Approximately 59.0% reported experiencing two to three symptoms of a disease; however, 56.3% of the respondents utilized healthcare services at most four times for the past six months. Most of the respondents were unaware that they automatically receive PhilHealth coverage in accredited healthcare facilities in the Philippines. Multiple regression analysis revealed that age, sex, family size, monthly income, geographical area, lifestyle factors, and awareness of health insurance were significant determinants of healthcare utilization. The findings revealed the impact of socio-demographic, lifestyle, and health insurance awareness on healthcare utilization among senior citizens. Policymakers and local government units may consider improving the capability for senior citizens to access health services, such as providing health insurance awareness programs and developing health-promoting activities.
Keywords: Health; Healthcare Utilization; Filipino Senior Citizens; Davao City; Philippines